Tegaren’s Constraints in Adapting Digital Technology to Its Tourism Development - Nuryananda, Praja Firdaus; Dwiridotjahjono, Jojok; Wahyuningtyas, Dwi (Future Science, 2023)
The article serves as a scholarly publication summarizing field research conducted in Tegaren, East Java. The research team's objective is to provide a fresh perspective on the digitalization of the tourism village. The article examines the challenges faced by Tegaren in enhancing digital telecommunications penetration and adapting to digital technology following its transformation into a tourism village. These challenges encompass four main factors: 1) the prevalence of a younger, less productive age group in Tegaren, 2) the departure of youth from Tegaren, 3) Tegaren's agricultural lifestyle and ecosystem, and 4) its geographically distant position from major transportation hubs. Employing a theoretical framework incorporating methods such as participatory rural assessment, asset-based community development, community-based tourism, and the digital culture and literacy of rural communities, the article elucidates the demographic and geographical obstacles hindering Tegaren's efforts to enhance digitalization for the tourist village. All data presented is derived from in-depth interviews and participatory observations carried out by the research team. The respondents comprise various stakeholders from the village, including village officials, Pokdarwis members, BUMDes members, besek farmers, and village youths. This article unveils a correlation between the evolution of a tourism village and the presence of shared spaces fostering creativity and productivity. Recognizing the distinctiveness inherent in the circumstances of each tourism village, it becomes clear that comprehensive generalizations about tourism village studies are not entirely applicable.